Pengaruh Penggunaan Kompres Hangat terhadap Intesitas Nyeri Persalinan Kala I Fase Aktif di PMB Nursehan Dahliana Birayang Banjarmasin Kalimantan Selatan - Mutia Annisa Putri; Anik Purwati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Childbirth causes pain due to shortening of the uterine muscles. Normal childbirth occurs because of pain, which is an important part of labor. During labor, pain can influence uterine contractions through the secretion of catecholamines and cortisol. It improves the function of the sympathetic nervous system, changing blood pressure, heart rate, breathing, and length of labor. The aim of this research is to find out how warm compresses impact how severe the pain of labor during the first active phase is. This research design is pre-experimental with a one group pre test and post test design. The population in this study were all mothers giving birth at BPM Nursehan Dahliana Birayang (Hulu Sungai Tengah Regency, South Kalimantan Province), using an accidental sampling technique and a sample size of 30 respondents was obtained. A warm compress is placed on the lower abdomen using a hot bladder. Data analysis used the Paired T - test. Based on the research results obtained, the average pain score before treatment was 8.13 and the average pain score after treatment was 4.66. The results of statistical analysis of tests of differences in pain intensity before and after treatment showed significant differences (p=0.000; 95% CI -3.900-(-3.031). The conclusion of this study is: warm compresses can reduce the intensity of labor pain in the active phase of the first stage. Warm compresses can be used as a way to reduce the intensity of labor pain.